Age matters: Fate of soil organic matter during ageing of earthworm casts produced by the anecic earthworm Amynthas khami. (September 2020) - Bottinelli, N.; Kaupenjohann, M.; Märten, M.; Jouquet, P.; Soucémarianadin, L.; Baudin, F.; Tran, T.M.; Rumpel, C.
Abstract: The transformation of organic matter (OM) occluded in earthworm casts during the casts' lifetime may affect its composition and accumulation in stabilised OM pools. We collected casts produced by the anecic earthworm Amynthas khami in a tropical woodland of Northern Vietnam presenting different degradation stages. The aim of this study was to assess (1) the biogeochemical properties of OM in earthworm casts compared to control aggregates from the surrounding soil, and (2) the fate of occluded OM during cast ageing. We analysed intact casts and their density fractions at five ageing stages for organic carbon (OC) and nitrogen (N) content, OM chemical composition by analytical pyrolysis, and OM stability by Rock-Eval thermal analysis. Compared to control aggregates, fresh casts had higher OC values (5.3 vs. 2.6%) and increased OC in all density fractions. Cast OM had more lignin (1.1 vs.< 0.1%), similar polysaccharide and N-compound contribution and was more thermally labile than those of control aggregates. Changes in OM composition and content during cast ageing appeared at the end of the casts' lifetime, when they were broken into smaller aggregates (10–13 mm). At these latest stages, OC content decreased (1.5-fold); along with OM in macro-aggregates (2.2-fold) and microaggregates (6.8-fold). Reduced mineral-associated OC was also recorded (1.3-fold). During ageing, the percentage of lignin decreased (5.5-fold) while the thermal stability of OM increased. The distinct OM properties of casts were maintained throughout the cast ageing process, and most properties of the oldest casts were significantly different from the control aggregates. Since OM is retained in cast fragments after they disintegrate, the earthworm influence on soil organic matter stabilisation processes appears to persist beyond the lifespan of casts. Graphical abstract: Image 1 Highlights: Earthworm casts had higher organic matter in all physical soil fractions. Earthworms changed chemical composition and thermal stability of soil organic matter. Significant changes of biogeochemical properties occurred after disintegration of cast. Organo-mineral associations are not stable during cast's lifetime